2007
DOI: 10.1016/j.cell.2007.08.029
|View full text |Cite|
|
Sign up to set email alerts
|

Exonuclease-1 Deletion Impairs DNA Damage Signaling and Prolongs Lifespan of Telomere-Dysfunctional Mice

Abstract: Exonuclease-1 (EXO1) mediates checkpoint induction in response to telomere dysfunction in yeast, but it is unknown whether EXO1 has similar functions in mammalian cells. Here we show that deletion of the nuclease domain of Exo1 reduces accumulation of DNA damage and DNA damage signal induction in telomere-dysfunctional mice. Exo1 deletion improved organ maintenance and lifespan of telomere-dysfunctional mice but did not increase chromosomal instability or cancer formation. Deletion of Exo1 also ameliorated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
93
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 71 publications
16
93
1
Order By: Relevance
“…For example, inactivation of Exo1 could facilitate escape from senescence and proliferation of mammalian cells with telomere defects. However, deletion of Exo1 did not appear to be a risk factor for cancer in mice lacking telomerase (Schaetzlein et al ., 2007). Conversely, Exo1 may instead facilitate genomic alterations relevant to carcinogenesis in DNA‐damaged human cells, similarly to its role in PAL cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inactivation of Exo1 could facilitate escape from senescence and proliferation of mammalian cells with telomere defects. However, deletion of Exo1 did not appear to be a risk factor for cancer in mice lacking telomerase (Schaetzlein et al ., 2007). Conversely, Exo1 may instead facilitate genomic alterations relevant to carcinogenesis in DNA‐damaged human cells, similarly to its role in PAL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has recently been shown that a SNP in the EXO1 promoter leading to higher levels of EXO1 expression is enriched in female centenarians (Nebel et al 2009), suggesting a possible role for EXO1 activity in prevention of premature ageing, possibly by reducing cancer risk. By contrast, deletion of the nuclease activity of EXO1 in short-lived lategeneration telomerase-deficient mice rescues lifespan (Schaetzlein et al 2007). This rather unexpected finding may result from repression of the cyclinkinase inhibitor p21, which leads to the increased lifespan in terc −/− mice, as observed in mice lacking other components of MMR such as PMS2 (SieglCachedenier et al 2007) and which directly phenocopies p21 −/− Terc −/− mice (Choudhury et al 2007).…”
Section: Replication Fidelity Is Enhanced Through Nucleases Acting Inmentioning
confidence: 99%
“…Discovered in yeast (4), Exo1 participates in recombination (4,5), telomere maintenance (6, 7), mismatch repair (2,3,8), and processing of stalled replication forks (9). Consistent with its recombination function, mice devoid of Exo1 demonstrate a reduction in ssDNA formation at DSBs (7). Although RecJ and Exo1 have the same DNA degradation polarity, they differ in substrate specificity: RecJ acts preferentially on ssDNA (10), whereas Exo1 acts on dsDNA (4).…”
mentioning
confidence: 99%